Development of Problem-Based Learning Oriented Electronic Worksheets (e-worksheets) to Improve Students' Critical Thinking Skills on Salt Hydrolysis Material - Sania Ayu Puspita; Harun Nasrudin (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to obtain problem-based learning-oriented e-worksheets that are feasible to improve students' critical thinking skills on salt hydrolysis material. This research uses Thiagarajan's 4D method, limited to the development stage. The feasibility of e-worksheets is reviewed from three aspects: validity, practicality, and effectiveness. The limited trial was conducted in class XI-12 State High School 1 Sidoarjo with 37 students. The research data showed that The e-worksheets are declared valid, indicated by the mode of content validity and construct validity of 5 with a very valid category. The e-worksheets are declared practical, indicated by the average results of student response questionnaires of 94% with a very practice category supported by the results of student activity observations. The e-worksheets are declared effective, indicated by the average posttest score higher than the pretest score with N-Gain Score of 0.76 in the high category. The paired sample t-test results showed a significance value of 0.000, indicating a significant difference between pretest and posttest scores. The research findings show that e-worksheets focusing on problem-based learning can be used to improve student's critical thinking skills in learning salt hydrolysis material.